A Review on Automatic Text Summarization Techniques in NLP - kaur, Kirtipreet; Kaur, Deepinderjeet (International Journal of Computer Sciences and Engineering, 2025)
In this article we present a survey on different text summarization techniques in natural language processing. Text Summarization is condensing the source text into a shorter version preserving its information content and overall meaning. It is very difficult for human beings to manually summarize large documents of text. There are many techniques of doing text summarization i.e. some are extractive as well as abstractive techniques. But we need that technique which will give meaningful summary without showing any redundancy or any type of ambiguity whether the summary will contain original text or not.